Changes in Lipids and Lipoproteins after Selective LDL Apheresis (7-Year Experience). (24th January 2012) - Kolovou, Genovefa; Hatzigeorgiou, Georgios; Mihas, Constantinos; Gontoras, Nikos; Litras, Panagiotis; Devekousos, Dimitris; Kontodima, Panagiota; Sorontila, Constantina; Bilianou, Helen; Mavrogeni, Sophie
Abstract : Background . The aim of the study was to investigate the changes in plasma lipids and lipoproteins and the cardiovascular events after selective LDL apheresis. Methods and Results . Two pediatric patients with familial hypercholesterolemia aged 11 and 13 years and 19 dyslipidemic adults aged 41 ± 14 years underwent direct adsorption of lipoproteins (DALI) sessions. The mean follow-up period was 47 ± 23 months. The total cholesterol (TC) values before and after treatment were 8.2 ± 2.2 and 3.1 ± 1.6 mmol/l (318 ± 86 and 122 ± 62 mg/dL), respectively. The interval mean of TC was 6.9 ± 1.9 mmol/l (268 ± 75 mg/dL). The LDL cholesterol concentrations before and after treatment were 6.6 ± 2.1 and 1.7 ± 1.1 mmol/l, (256 ± 82 mg/dL and 65 ± 41 mg/dL), respectively. The percentage of acute LDL cholesterol reduction was 75 ± 11%. Cardiovascular events were observed in seven patients. The average annual event rate was 5.51%. Conclusion . LDL apheresis is a very important therapeutic tool in managing patients at high risk for premature CAD or with aggressive CAD, despite adequate medical treatment.